PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 1 BUKIT BATU KABUPATEN BENGKALIS - Leica Oktaviani; Gustimal Witri; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the effect of applying the cooperative learning model of the talking stick type to the results of mathematics learning in fifth grade students of SD Negeri 1 Bukit Batu Bengkalis Regency. This type of research is a Quasi Experimental Design with Nonequivalent Control Group Design. The subjects of this study were all students in class V, Va class totaling 20 people as the experimental class and Vb class totaling 18 people as the control class. Data collection techniques using tests. Instruments for measuring learning outcomes using pretest and posttest in the form of objective tests. The data analysis technique uses the t test. The results of the study on the control class of the pretest value obtained an average of 36.66 and the posttest value of 57.77 while in the experimental class the value of the pretest was 33.50 and the posttest value was 70.25. The results of the hypothesis test indicate that the value of 〖t 〗_count ≥ t_table or 4.33 ≥ 1.69 is obtained. This shows that the application of the cooperative learning model of the talking stick type influences the results of mathematics learning in fifth grade students of SD Negeri 1 Bukit Batu, Bengkalis Regency.Key Words: Talking Stick, Mathematics Learning Outcomes